Rodent Models for the Analysis of Tissue Clock Function in Metabolic Rhythms Research - Tsang, Anthony H.; Astiz, Mariana; Leinweber, Brinja; Oster, Henrik (Frontiers in Endocrinology, 2017)
The circadian timing system consists on a distributed network of cellular clocks that together coordinate 24-hour rhythms of physiology and behaviour. Clock function and metabolism are tightly coupled, from the cellular to the organismal level. Genetic and non-genetic approaches in rodents have been employed to study circadian clock function in the living organism. Due to the ubiquitous expression of clock genes and the intricate interaction between the circadian system and energy metabolism, genetic approaches targeting specific tissue clocks has been used to assess their contribution in systemic metabolic processes. However, special requirements regarding specificity and efficiency have to be met to allow for valid conclusions from such studies. In this review we provide a brief summary of different approaches developed for dissecting tissue clock function in the metabolic context in rodents, compare their strengths and weaknesses and suggest new strategies in assessing tissue clock output and the consequences of circadian clock disruption in vivo.